El perro vagabundo - Simont, Marc (New York : Rayo, 2003)
A family befriends a stray dog, names him Willy, and decides to keep him.
"Basado en un relato veridico de Reiko Sassa."
Accelerated Reader
Keywords: Dogs -- Juvenile fiction; Perros -- Novela juvenil